Предмет: Алгебра, автор: kitysswrq1

1. 1) a) 2) a) 3) а) 4) a) 5) a) Сократите x(a+3) y(a +3) 3a + 3b 5(a+b) 2(x-y) x(y-x) 5x−10 x2 - 4 у2 - 16 Ay2 - y3 ; б) б) ; б) ; б) 6) дробь: 3(x + 5)² (x+5)3 7x-14y 3x-6y 3c-9d 6d-2c a2 - 9 15+5a ; ; a² - 2a +1 1 - a2 1; B) B) B) B) в) 3a (b-2) 6 (b-2)² 5а-20с 15ac a2 - 2ab - 6b - 3а x2-4x+4 3x-6 4; m3 + 8 2 m² - 2mn +4​

Приложения:

Ответы

Автор ответа: drtovski
2

Объяснение:

a)

x(a+3) = x * (a + 3)

a)

y(a +3) = y * (a + 3)

а)

3a + 3b = 3(a + b)

a)

5(a+b) = 5 * (a + b)

a)

2(x-y) = 2 * (x - y)

a)

x(y-x) = x * (y - x)

a)

5x−10 = 5 * (x - 2)

a)

x² - 4 = x² - 2²

a)

y² - 16 = y² - 4²

a)

Ay² - y³ = y²(A - y)

б)

3(x + 5)² = 3 * (x + 5)²

б)

(x+5)³ = (x + 5)³

б)

7x-14y = 7(x - 2y)

б)

3x-6y = 3(x - 2y)

б)

3c-9d = 3(c - 3d)

б)

6d-2c = 2(3d - c)

б)

a² - 9 = a² - 3²

б)

15+5a = 5(3 + a)

в)

a² - 2a +1 = (a - 1)²

в)

1 - a² = 1 - a²

в)

3a (b-2) = 3a * (b - 2)

в)

6 (b-2)² = 6 * (b - 2)²

в)

5а-20с = 5a - 4 * 5c

в)

15ac = 15ac

в)

a² - 2ab - 6b - 3а = a² - 3a - 2ab - 6b

в)

x²-4x+4 = (x - 2)²

в)

3x-6 = 3(x - 2)

в)

4 = 4

в)

m³ + 8 = m³ + 2³

в)

2 m² - 2mn + 4 = 2(m² - mn + 2)


ustinovakarina58459: и как это понимать?
Похожие вопросы
Предмет: Математика, автор: alla1542fa